The Bay of Biscay as a sphere of interaction (2900-1100 BC): big data and big thinking in the Bronze Age - Latorre-Ruiz, J (2021)
This study is about the flow of metalwork around the Bay of Biscay between the Chalcolithic and the Middle Bronze Age. The Bay of Biscay is understood as the waterbody between northern Iberia and western Atlantic France. This study addresses three questions. How were the different regions of the Bay of Biscay connected to each other during the Bronze Age, what routes were used to travel between them and what was the nature of the connections identified? To answer them in Chapter 2 the routes employed to travel around the Bay in the longue-durée are identified. In Chapters 3, 4 and 5 the distribution of metalwork is analysed to understand how the Bay’s regions were connected to each other during the periods studied. Finally, Chapter 6 discusses the possible nature of those connections and what routes might have been employed at the different moments of the Bronze Age.